The Implementation of The Policy on School Operational Assistance (BOS) at Junior High Schools in Indragiri Hilir Riau Indonesia - Yesrahmatulah Yesrahmatulah; Iqbal Miftakhul Mujtahid; Sofjan Arifin (Universitas Terbuka, 2021)
BOS policy is one of the public policies made by the government aiming at improving the quality of human resources as the indicator of the progress of a nation's development. This study aimed at analyzing and describing BOS policy, the implementation of BOS funds, and the supporting factors and inhibiting factors in implementing BOS policy at Junior High Schools in the Tembilahan sub-district. This study design was qualitative using a descriptive method. The data and information were collected through an observation technique, interview, and documentation. Data analysis was conducted using classification steps, analysis, and data interpretation until the conclusion was drawn. The result showed that the BOS policy was an appropriate and effective public policy for people in general and, particularly, for the school, teaching staff, and the students. Regarding the implementation of the BOS policy at Public Junior High Schools in the Tembilahan sub-district, it was good and met the BOS technical guideline. However, it still had an obstacle that several school activities could not be accommodated using BOS funds. The supporting factors of the BOS policy implementation at Public Junior High Schools in the Tembilahan sub-district were good communication between several relevant parties and the availability of competent human resources. Meanwhile, the inhibiting factors were financial resources and the characteristics of the policy were too rigid in the use in every school.